RESPON PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir)TERHADAP PEMBERIAN PUPUK ORGANIK DI LAHAN SAWAAH DESA KELONDOM - Agus Burhan (Sekolah Tinggi Pariwisata Mataram, 2022)
The aim of this research is to Know the Growth Response of Kale Kale (Ipomoea Reptans Poir) Towards Organic Fertilizer Giving in Kelondom Village Rice Field. This research was conducted in Kelondom Village, Galang District, Tolitoli Regency. The time to carry out this research for three months from February to April 2020. This research was compiled using a Randomized Block Design (RBD) consisting of 5 levels, namely: A0 = No fertilizer (control), A1 = Dose of fertilizer 2 ml / liter , A2 = Dose of Fertilizer 3 ml / liter, A3 = Dose of Fertilizer 4 ml / liter, A4 = Dose of Fertilizer 5 ml / liter. Each treatment was repeated three times so that there were 15 study plots. If the results of analysis of variance show a real effect, then a further test will be conducted using the Honestly Significant Difference test (BNJ) at the 5% level. The results showed that the application of liquid organic fertilizer 5 ml / liter significantly affected plant height aged 1, 2, 3 and 4 weeks after planting, the number of leaves aged 1 and 2 weeks after planting, the length of leaves aged 1.2 and 4 weeks after planting , while at the age of 3 weeks after planting has a very significant effect on the number of leaves of kale. The application of liquid organic fertilizer 5 ml / liter significantly affects root volume, root length and plant wet weight.